Symmetry-Breaking Charge-Transfer Chromophore Interactions Supported by Carbon Nanodots - Cacioppo, Michele; Scharl, Tobias; Dordevic, Luka; Cadranel, Alejandro; Arcudi, Francesca; Guldi, Dirk Michael; Prato, Maurizio (Angewandte Chemie International Edition, 2020)
Carbon dots (CDs) and their derivatives are useful platforms for studying electron-donor/acceptor interactions and dynamics therein. Herein, we couple amorphous CDs with phthalocyanines (Pcs) that act as electron donors with a large extended pi-surface and intense absorption across the visible range of the solar spectrum. Investigations of the intercomponent interactions by means of steady-state and pump-probe transient absorption spectroscopy reveal symmetry-breaking charge transfer/separation and recombination dynamics within pairs of phthalocyanines. The CDs facilitate the electronic interactions between the phthalocyanines. Thus, our findings suggest that CDs could be used to support electronic couplings in multichromophoric systems and further increase their applicability in organic electronics, photonics, and artificial photosynthesis.
CRIS-Team WoS Importer:2020-05-29